Analisis Pengembangan UMKM di Era New Normal Dengan Prinsip Syariah - Aulia Rahman; Deery Anzar Susanti; Asmawarna Sinaga (AGHNIYA : Jurnal Ekonomi Islam, 2021)
This study describes the development of Micro, Small and Medium Enterprises (UMKM) which are currently affected by the COVID-19 outbreak that is spreading in Indonesia. This study also reveals how UMKM should be able to continue to survive and develop, so that the economic sector in Indonesia can continue to survive. Because, UMKM are a foundation in maintaining economic resilience in Indonesia. This research is a descriptive qualitative research, where later the author describes the method that must be used in business development. As for the results obtained, that the development of UMKM must of course be based on sharia principles, which in sharia principles enter into agreements or use mudharabah contracts or profit sharing systems, and utilize technology that is currently developing